HUBUNGAN INFILTRASI LIMFOSIT PADA PROSTAT DENGAN RETENSI URINE PADA BENIGN PROSTATIC HYPERPLASIA DI RSUD ULIN BANJARMASIN - Muhammad Abianovan Ramadhan; Hendra Sutapa; Ika Kustiyah Oktaviyanti; Eka Yudha Rahman; Ida Yuliana (Homeostasis, 2022)
Benign prostatic hyperplasia (BPH) is a common condition in elderly men. BPH may cause lower urinary tract symptoms (LUTS) and urinary retention. Chronic inflammation is a common founding in histological examination of BPH and related to a higher risk of urinary retention. The purpose of this study is to analyze the association between lymphocyte infiltration in prostate and urinary retention in BPH in Ulin General Hospital Banjarmasin. This is an analytic observational study with cross sectional approach. There are 78 samples, collected by purposive sampling method. There are 47 (60,26%) patients diagnosed with urinary retention, while 31 (39,74%) others are diagnosed with LUTS. Lymphocyte infiltration is found in 68 (87,18%) specimens, consist of 20 (25,64%) specimens of BPH with mild inflammation, 34 (43,59%) specimens of BPH with moderate inflammation, and 14 (17,95%) specimens of BPH with severe inflammation. There is no lymphocyte infiltration found in 10 (12,82%) specimens. The result of the analysis is P = 0,320. The conclusion of this study is that there is no significant association between lymphocyte infiltration in prostate and urinary retention in BPH in Ulin General Hospital Banjarmasin